2019
DOI: 10.1002/jcb.29307
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CCAT1 functions as apoptosis inhibitor in podocytes via autophagy inhibition

Abstract: Podocyte apoptosis importantly contributes to various kidney diseases. Long noncoding RNAs Colon cancer‐associated transcript‐1 (CCAT‐1) has been demonstrated for a critical role in cell proliferation. In the present study, the relationship between CCAT1 and popdocyte impairment, and the underlying mechanism was investigated. Podocytes were isolated from mice and then treated with tumor necrosis factor‐α to simulate podocyte injury. After developed CCAT1 overexpression or knockdown, cell viabilities were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…It is also worth mentioning here that stimulation of inflammation might give rise to trigger apoptosis [80]. In this regard, TNF-α may stimulate apoptosis via TNF receptor or death receptor, thereby activate the extrinsic pathway of apoptosis [81]. This elucidation is supported by the results of the present study which revealed that doxorubicin injection stimulates the expression of pro-apoptotic mediator in the intrinsic pathway of apoptosis (Fig.…”
Section: Histological Changessupporting
confidence: 77%
See 1 more Smart Citation
“…It is also worth mentioning here that stimulation of inflammation might give rise to trigger apoptosis [80]. In this regard, TNF-α may stimulate apoptosis via TNF receptor or death receptor, thereby activate the extrinsic pathway of apoptosis [81]. This elucidation is supported by the results of the present study which revealed that doxorubicin injection stimulates the expression of pro-apoptotic mediator in the intrinsic pathway of apoptosis (Fig.…”
Section: Histological Changessupporting
confidence: 77%
“…fasciata. As p53 is an intermediate in the intrinsic pathway of apoptosis that was triggered by oxidative stress [5,81,116] and TNF-α triggers extrinsic apoptosis via cell death/TNF receptors [5], this led us to suggest that U. fasciata and AgNPs/U. fasciata may decrease apoptosis in doxorubicinadministered rats through affecting both intrinsic and extrinsic apoptotic pathways (Fig.…”
Section: Histological Changesmentioning
confidence: 99%
“…Most studies suggest that autophagy plays a protective role in podocytes (Ye et al, 2019), but some scientists hold different views. Su et al (2020) have demonstrated that autophagy is involved in podocyte apoptosis caused by tumor necrosis factora (TNF-a), and some IncRNAs can exert anti-apoptotic effects via inhibiting autophagy. It is remarkable that podocyte apoptosis and autophagy activation often appear together.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA colon cancer-associated transcript-1 (CCAT1) is closely associated with a variety of cancers. A recent study has clearly shown that lncRNA CCTA1 induced autophagy inhibition for cell survival via increasing PI3K/AKT pathway in podocytes [ 110 ]. LINC00470, known as C18orf2, also activates AKT signaling, inhibits cell autophagy and promotes glioblastoma cell tumorigenesis and poor patient prognosis [ 111 ].…”
Section: Mechanisms Of Autophagymentioning
confidence: 99%